McMaster RARE‐Bestpractices clinical practice guideline on diagnosis and management of the catastrophic antiphospholipid syndrome. (5th July 2018) - Legault, K.; Schunemann, H.; Hillis, C.; Yeung, C.; Akl, E. A.; Carrier, M.; Cervera, R.; Crowther, M.; Dentali, F.; Erkan, D.; Espinosa, G.; Khamashta, M.; et al.
Abstract : Summary: Background: The McMaster RARE‐Bestpractices project group selected the catastrophic antiphospholipid syndrome (CAPS) for a pilot exercise in guideline development for a rare disease. Objectives: The objectives of this exercise were to provide a proof of principle that guidelines can be developed for rare diseases and assist in clinical decision making for CAPS. Patients/Methods: The GIN‐McMaster Guideline Development checklist and GRADE methodology were followed throughout the guideline process. The CAPS guideline was coordinated by a steering committee, and the guideline panel was formed with representation from all relevant stakeholder groups. Systematic reviews were performed for the key questions. To supplement the published evidence, we piloted novel methods, including use of an expert‐based evidence elicitation process and ad hoc analysis of registry data. Results: This paper describes the CAPS guideline recommendations, including evidence appraisal and discussion of special circumstances and implementation barriers identified by the panel. Many of these recommendations are conditional, because of subgroup considerations in this heterogeneous disease, as well as variability in patient values and preferences. Conclusions: The CAPS clinical practice guideline initiative met the objective of the successful development of a clinical practice guideline in a rare disease using GRADE methodology. We expect that clinicians caring for patients with suspected CAPS will find the guideline useful in assisting with diagnosis and management of this rare disease.